2021
DOI: 10.1080/2331186x.2021.1984628
|View full text |Cite
|
Sign up to set email alerts
|

What promotes adolescents’ sense of school belonging? Students and teachers’ convergent and divergent views

Abstract: In this study, which endeavored to identify school climate factors and their influence on adolescent students' feelings of school belonging, it became evident that a new conceptualization thereof is needed. Quantitative data from 443 male and female 11 th graders and 264 of their teachers and qualitative data from 16 students and eight of their teachers in Al Ain public school district were collected. The findings revealed that adolescents perceived parental involvement, classroom practices, teacher-student re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
(38 reference statements)
0
9
0
Order By: Relevance
“…This could be attributed to the different ways early adolescents and later adolescents reacted to socialization due to a variety of factors, including developmental changes (Krishnan, 2010). However, El Zaatari and Ibrahim (2021) as well showed that there is no statistically significant difference in the sense of belonging between boys and girls in Grade 11. Sánchez et al (2005) also saw no significant differences in the sense of belonging between boys and girls in Grade 12, a result that contradicts findings based on middle-school students’ performance.…”
Section: The Bio-ecological System Theoryand School Belongingmentioning
confidence: 93%
See 4 more Smart Citations
“…This could be attributed to the different ways early adolescents and later adolescents reacted to socialization due to a variety of factors, including developmental changes (Krishnan, 2010). However, El Zaatari and Ibrahim (2021) as well showed that there is no statistically significant difference in the sense of belonging between boys and girls in Grade 11. Sánchez et al (2005) also saw no significant differences in the sense of belonging between boys and girls in Grade 12, a result that contradicts findings based on middle-school students’ performance.…”
Section: The Bio-ecological System Theoryand School Belongingmentioning
confidence: 93%
“…For example, when an education system aims to achieve internationally competitive educational outcomes by ranking among the top countries in international exams, the national and local education policies within the school exosystem will apply an exam-oriented approach that could affect the school microsystem's practices, curriculum, teaching strategies, and the student evaluation system. Such changes appear to influence the overall school climate and would indirectly impact the development of school belonging (El Zaatari & Ibrahim, 2021).…”
Section: The Bio-ecological System Theory and School Belongingmentioning
confidence: 99%
See 3 more Smart Citations